2002
DOI: 10.2320/matertrans.43.1670
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Rate Evaluation for Bulk Amorphous Alloys from Eutectic Microstructures in Casting Processes

Abstract: The structural features of metallic glasses depend on the cooling rate of the melt. The cooling rates for casting processes which are typically employed for preparation of bulk metallic glasses are suggested from microstructures of an eutectic Al-33 mass%Cu model alloy. The interlamellar spacing λ of eutectic Al-CuAl 2 rod-shaped specimens of 50 mm in length and 2 to 5 mm in diameter has been determined by optical microscopy and scanning electron microscopy. From the measured interlamellar spacings ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 17 publications
1
50
1
1
Order By: Relevance
“…36 It is well known that the cooling rate decreases from the surface towards the center of the cast rods. 42 The observed microstructural features found for the 2 and 3-mmл rods suggest that these featureless darker regions are more pronounced near the specimen surface of the cylinders, which is completely the opposite of what one should expect. Rather, a mostly glassy structure is expected to form near the Cu-mold surface due to the higher cooling rate realized close to the mold, and crystalline phases should appear at the center of the specimen.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…36 It is well known that the cooling rate decreases from the surface towards the center of the cast rods. 42 The observed microstructural features found for the 2 and 3-mmл rods suggest that these featureless darker regions are more pronounced near the specimen surface of the cylinders, which is completely the opposite of what one should expect. Rather, a mostly glassy structure is expected to form near the Cu-mold surface due to the higher cooling rate realized close to the mold, and crystalline phases should appear at the center of the specimen.…”
Section: Methodsmentioning
confidence: 51%
“…It has been reported that the cooling rate across the length of a rod decreases from the bottom to the top of the rod. 42 Even though the bulk glass formation of 5-mm-diameter rods for this alloy composition has been reported, 44 we found that the solidified microstructure can vary from glassy to fully crystalline (Figs. 2 and 5) and strongly depends on the actual cooling rate adopted along the length of the rod.…”
Section: Methodsmentioning
confidence: 83%
“…A typical microstructure of Cu 47 Zr 47 Al 6 AMI is presented in Fig. 1 22) exhibit a glassy structure, as proved by XRD ( Fig. 1(d)), DSC and TEM.…”
Section: Methodsmentioning
confidence: 97%
“…2a,d) composed of nearly stoichiometric khatyrkite (CuAl 2 , containing 0.8% Fe) and Al metal (containing 1% Cu). This texture is known to occur as a result of rapid cooling (B10 2 -10 3°C s À 1 ) of liquids in the Al-Cu system [16][17][18] . showing that the matrix was the precursor for the shocked silicates.…”
Section: Resultsmentioning
confidence: 99%